2009
DOI: 10.1128/aac.00505-09
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone and Miltefosine Act Synergistically against Leishmania mexicana and Can Induce Parasitological Cure in a Murine Model of Cutaneous Leishmaniasis

Abstract: Leishmaniasis is parasitic disease that is an important problem of public health worldwide. Intramuscularly administered glucantime and pentostam are the most common drugs used for treatment of this disease, but they have significant limitations due to toxicity and increasing resistance. A recent breakthrough has been the introduction of orally administered miltefosine for the treatment of visceral, cutaneous, and mucocutaneous leishmaniasis, but the relative high cost and concerns about teratogenicity have li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 21 publications
(25 reference statements)
3
30
0
1
Order By: Relevance
“…In Veiga-Santos et al study (2012), it was found that the combination of AMD and posaconazole exhibit potent synergistic activity against T. cruzi (33). In Serrano Martin et al (2009) investigation, AMD and miltefosine combination had synergistic inhibitory effects on the proliferation of intracellular amastigotes (29). Results of the present study indicate that AMD and KTZ act synergistically gainst L. infatum for the first time.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In Veiga-Santos et al study (2012), it was found that the combination of AMD and posaconazole exhibit potent synergistic activity against T. cruzi (33). In Serrano Martin et al (2009) investigation, AMD and miltefosine combination had synergistic inhibitory effects on the proliferation of intracellular amastigotes (29). Results of the present study indicate that AMD and KTZ act synergistically gainst L. infatum for the first time.…”
Section: Discussionsupporting
confidence: 55%
“…Inactivation of Ca 2+ and K + channel is the mechanism of its antiarrhythmic action in mammals. Also, antiparasitic effects of AMD have been claimed (12,13,29) as well as a broad-spectrum antifungal action (30). Interfering with mitochondrial membrane potential (∆Ψm), inhibition of sterol biosynthesis, Ca 2+ homeostasis disordering as well as reactive oxygen species production are the main mechanisms of action of AMD against different organisms (12,13,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group showed the potent in vitro effects of itraconazole and posaconazole against Leishmania amazonensis (17). Benaim et al (47) demonstrated the specific antiparasitic effects of amiodarone and the synergistic effects of combinations with posaconazole against Trypanosoma cruzi, in vitro and in vivo; similar effects were more recently reported for Leishmania mexicana and miltefosine (48). There is a growing recognition of the relevance of combination therapies to address several limitations of currently available antiLeishmania drugs, including toxicity as well as natural and acquired drug resistance (1,3,(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 51%
“…Various compounds have been tested, combined with glucantime, in order to improve chemotherapy 7,9,14,[21][22][23]26,28,30,34 , and the rationale behind combining drugs and therapies allows the reduction of treatment duration, resulting in fewer side effects and fewer delays in the development of resistance 8,34 . This report describes the effect of the combined therapy of HBO and glucantime against intracellular amastigotes in vitro and against infection in mouse model BALB/c.…”
Section: Introductionmentioning
confidence: 99%